Get your sh*t together : how to stop worrying about what you should do so you can finish what you need to do and start doing what you want to do - Knight, Sarah (New York : Little, Brown and Company, 2017)
Provides a straight-talking, humorous, and helpful guide to shedding self-doubt and finding one's own path to success.
"A no f*cks given guide"--Cover.
Keywords: Conduct of life -- Humor; Self-help techniques -- Humor; Conduct of life -- Humor.2sears.; Self-help techniques -- Humor